Intertidal history in island Southeast Asia submerged genealogy and the legacy of coastal capture - Gaynor, Jennifer L. (Southeast Asia Program Publications, an imprint of Cornell University Press, 2016)
Intertidal History in Island Southeast Asia shows the vital part maritime Southeast Asians played in struggles against domination of the seventeenth-century spice trade by local and European rivals. This history of shifting political and interethnic ties among the people of Sulawesi's littorals and its land-based realms, along with their shared interests on distant coasts, exemplifies how regional maritime dynamics interacted with social and political worlds above the high-water mark.